Implementation of Problem Based Learning Model in Improving Students' Mathematics Learning Outcomes at MI Hidayatun Najah - Latifah, Vivi Nur; Oktaviani, Vivi; Kui, Wa; Kodi, Wa; Kushardani, Vera (Jurnal Profesi Guru Indonesia, 2024)
This study aims to determine the effectiveness of the application of the Problem Based Learning (PBL) learning model in improving mathematics learning outcomes in data presentation materials in the form of bar diagrams of 3rd grade students of MI Hidayatun Najah Tuban. The background of this study is the low student learning outcomes caused by the lack of active participation and student involvement in the learning process. The PBL model was chosen because it can encourage students to think critically, collaborate, and be actively involved in solving contextual problems. This study uses a quantitative approach with a Class Action Research (PTK) design which is carried out in two cycles. The subjects of the study were 28 3rd grade students. Data collection techniques are carried out through observation, learning outcome tests, and documentation. The results of the study showed a significant improvement in student learning outcomes after the implementation of the PBL model. In the pre-cycle, the percentage of students who achieved the Minimum Completeness Criteria (KKM) was 36%, in the first cycle it increased significantly to 57% and the increase in the second cycle to 86%. In addition, an increase also occurred in student activities and participation during the learning process. Based on these findings, it can be concluded that the PBL learning model is effectively applied in mathematics learning, especially in the material of presenting data in the form of a bar diagram, to improve learning outcomes and student involvement.